Feasibility study on augmented supplier audit - Gottfried Obmann; Sascha Stradner (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Conventional supplier audits are outdated as traditional instruments in supplier management. At least since travel and contact restrictions were imposed due to Covid-19, digital instruments must be used for remote supplier audits. Augmented Reality (AR) technology supports international supply management to work more efficiently and sustainably. Methodology: For this purpose, the feasibility of Augmented Supplier Audit in Industry applications will be analyzed based on a literature review and use case research. The focus is on hardware/software, legal/normative specifications as well as procedural feasibility. First research findings are pictured in a use case and described in this paper. Findings: The study shows the high potential of Augmented Supplier Audit as a standardized instrument in industry. Nevertheless, there are barriers to consider. Beside the lack of appropriate software applications to execute a fully integrated Augmented Supplier Audit, data security and the provision of hardware at supplier side has to be defined. Originality: Current research activities on technology-supported supplier audit are primarily limited on video conferences, the prevalence of remote audits in practice is marginal. However, since the beginning of the corona pandemic, (re)-certification audits are either postponed or allowed to be held remotely, whereby first practical experience could be generated.
urn:nbn:de:gbv:830-882.0161965; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Supply Chain Risk Management; Supply Chain Security